Sustainable Development: Learning the Quran Using the Utrujah Mothod - Parera, Gebi Gita; Hendrisab, Hendrisab; Rahman, Ikhwan (Ahlussunnah: Journal of Islamic Education, 2024)
This study discusses the implementation of the Utrujah method in learning the Quran at Markaz Ashhabul Qur'an, Bukittinggi City. The Utrujah method is an integrative approach designed to facilitate children, especially those of an early age, in reading and memorizing the Quran in a fun and systematic way. The purpose of this study is to describe in depth how the planning, implementation, and evaluation of the Utrujah method is applied in the institution. The research approach used is qualitative with the type of field research, where data collection techniques are carried out through observation, interviews, and documentation. The research informants consisted of the head of the foundation, the principal, the vice principal, and the teaching female teachers. The results of the study indicate that: (1) the planning of the Utrujah method has been well designed through the preparation of adequate materials, strategies, and learning tools; (2) the implementation of the method is carried out in a structured manner through the practice of reading the hijaiyyah letters and tahsin guided directly by the teacher; (3) learning evaluation is carried out using oral and written tests to measure the memorization ability and quality of the students' reading. This research is expected to be an initial reference for further studies in the context of developing Al-Quran learning methods in various tahfidz institutions.